Updates on molecular and biochemical development and progression of prostate cancer - Fahmy, Omar; A. Alhakamy, Nabil; Y. Rizg, Waleed; Bagalagel, Alaa; J. Alamoudi, Abdulmohsin; M. Aldawsari, Hibah; M. Khateb, Aiah; M. Eldakhakhny, Basmah; A. Fahmy, Usama; H. Abdulaal, Wesam; G. Fresta, Claudia; Caruso, Giuseppe (MDPI, 2021)
Prostate cancer (PCa) represents the most commonly non-cutaneous diagnosed cancer in men worldwide and occupies a very wide area of preclinical and clinical research. Targeted therapy for any cancer depends on the understanding of the molecular bases and natural behaviour of the diseases. Despite the well-known effect of androgen deprivation on PCa, many patients develop resistance either for antiandrogen therapy or other new treatment modalities such as checkpoint inhibitors and chemotherapy. Comprehensive understanding of the development of PCa as well as of the mechanisms underlying its progression is mandatory to maximise the benefit of the current approved medications or to guide the future research for targeted therapy of PCa. The aim of this review was to provide updates on the most recent mechanisms regarding the development and the progression of PCa. According to the current understanding, future treatment strategies should include more predictive genetic and biomarker analysis to assign different patients to the expected most appropriate and effective treatment.